Entrepreneurial leadership questionnaire: confirmatory factor analysis evidence from school context - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah; Basri, Ramli; Hassan, Siti Aishah (International Organization of Scientific Research, 2017)
Objective: The main objective of the study is to ascertain the reliability of entrepreneurial leadership questionnaire (ELQ) among secondary schools in Zamfara State- Nigeria through teacher’s perspectives. Methodology: Structural equation modeling (SEM) AMOS using confirmatory factor analysis was adopted in this study. Total of 395 samples were chosen through multi stage random sampling technique as participants in the research. Data were collected through the administration of adopted instruments from previous researchers. Findings: The Data was analyzed using Structural Equation Modeling (SEM) with AMOS graphics. Preliminary and subsequent assessments of model fits were conducted which fell within the acceptable threshold, and indicates the data fits the model (762) = 1249.211, p=0.00, /DF=1.629, GFI=0.853; TLI=0.915, CFI=0.957; IFI=0.957, RMSEA= 0.042. Conclusion: The findings indicated that the ELQ was highly valid and reliable to measure entrepreneurial leadership practice among secondary school teachers in Zamfara state, Nigeria. by applying 2 t GML/ha combined with 0.25 t JITU−/ha for two seasons in long run.